MATHEMATICAL COMMUNICATION ABILITY OF CLASS X MIPA 1 MAN DONGGALA STUDENTS - Nurhalizah, Nurhalizah; Hadjar, Ibnu; Lefrida, Rita; Karniman, Tegoeh S (Universitas Sembilanbelas November Kolaka, 2023)
This type of research is a descriptive qualitative approach. The subjects in this research areClass X MIPA 1 MAN Donggala students consist of 4 people, each 2 male students and 2 female students who have FI cognitive style and FD cognitive style. Data on students' communication skills was obtained by written assignments and interviews. The results of the research show that the mathematical communication skills of students who have a Field Dependent cognitive style are less capable than men because they cannot achieve all the indicators. The student subject has a Field Dependent female cognitive style which is quite capable because it achieves one.The student subject has a Field Independent male cognitive style which is quite capable because it achieves two indicators.The student subject has a Field Independent female cognitive style that is capable of achieving all three indicators. So the conclusion obtained from this research is that students' mathematical communication abilities are generally said to be poor, this is because the majority of students have not met several indicators of the three indicators of students' mathematical communication abilities. This can be seen with only one student achieving all three indicators.